2018
DOI: 10.7224/1537-2073.2017-059
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Sexual Dysfunction in Individuals with Multiple Sclerosis

Abstract: Sexual dysfunction is highly prevalent in the MS clinic sample. Assessment and treatment of depression may serve as a starting point for intervention in patients with MS who experience sexual dysfunction. Identifying individuals who are at risk for sexual dysfunction concerns may help with clinician and patient burden in terms of routine assessment of this symptom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 13 publications
(12 reference statements)
3
20
1
Order By: Relevance
“…Sexual dysfunction is one of the common side effects of multiple sclerosis (MS) that usually goes unreported by patients and do not address by clinicians [16]. The prevalence of sexual dysfunction in MS patients had been estimated to be between 40% and 80 % [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sexual dysfunction is one of the common side effects of multiple sclerosis (MS) that usually goes unreported by patients and do not address by clinicians [16]. The prevalence of sexual dysfunction in MS patients had been estimated to be between 40% and 80 % [24].…”
Section: Discussionmentioning
confidence: 99%
“…According to ELIXIR study, 76 per cent of depressed participants suffer from arousal problems, and the other 24 per cent had problems with erectile or lubrication [33]. Physiological and psychological factors can cause depression symptoms in MS patients that require close monitoring and selecting appropriate treatment options such as behavioural and pharmacological approaches) [34]. Furthermore, using antidepressants by depressed patients may worsen the sexual dysfunction in them, as studies have confirmed the relation between antidepressants and sexual dysfunction [35], [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with multiple sclerosis (MS) usually experience an alteration in physiological and emotional health that can affect women’s sexual life. MS can influence sexual satisfaction and sexual activity that are often underreported and under-diagnosed [ 1 ].. Patients with MS might experience sexual dysfunction, sexual dissatisfaction, and problems in relationships with their partners.…”
Section: Introductionmentioning
confidence: 99%